Política de atenção à saúde bucal indígena : do modelo à prática dos serviços ofertados aos Xetá/PR - Sanchez, Carla Martins (2012)
This dissertation is the result of research carried out during the Masters in Public Health, wich aimed to understand and analyze the organization and provision of health services available to Xetá, by Special Indigenous Health Districts (SIHD), being SIHD South Interior and SIHD South Coast. In this dissertation, I try to present as it is being organized the oral health services available to Xetá, as these services are being offered to this community, what are the main oral health problems presented by them as well as the procedures and referrals along with the Base-Poles responsible, finally, if there is an oral health policy geared specifically to this community of survivors, people who were brutally removed from their traditional territory invaded by colonization fronts coffee in the 1950s. The research subjects were managers and professionals, one doctor and two dentists, who provide care for indigenous people, including the Xetá. Sought to bring to this dissertation the similarities and differences between the ‘model’, described in the documents of Ministry of Health, and the ‘practice’, performed within indigenous communities. And was possible to perceive, through the field research, that the principles of special attention, so well developed in official documents, are not yet a reality in the formation of multidisciplinary teams to work in multicultural situations, being this one of the factors that reaffirms the situation of invisibility of Xetá, that living as aggregates in Kaigang or Guarani lands, receive the same attention that is aimed to them. Nor is there one health care policy directed to ethnocultural diversity.